Knowledge, attitude and preventive practices regarding tuberculosis and its predictors among HIV patients in General Hospital, Minna, North-Central, Nigeria - Bisallah, Chindo Ibrahim; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina; Iliyasu, Zubairu; Lye, Munn Sann; Onyilo, Michael Ochigbo (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Tuberculosis is the commonest cause of death among HIV patients in Nigeria. Though tuberculosis is common among HIV patients, their knowledge about transmission and prevention is poor. Objective: To determine knowledge, attitude and preventive practices regarding tuberculosis and its predictors among HIV patients receiving treatment. Methods: A cross sectional study was carried out involving 226 randomly selected HIV patients receiving care at General Hospital, Minna. Study duration was from June 2015 to July 2017. Data on socio-demographic characteristics, psychosocial factors, knowledge, attitude and preventive practices regarding tuberculosis was collected using a self-administered, WHO modified, pretested and validated questionnaires. Data collected was analysed using SPSS version 22. Results: Out of 226 respondents, 60(26.5%) had poor knowledge, 123(54.4%) had negative attitude and 48(21.2%) had poor preventive practices regarding tuberculosis. The predictors of knowledge were age (B=0.087, 95%CI=0.031, 0.143, p=0.002), depression (B=-0.444, 95%CI=-0.673,-0.214, p<0.001) monthly income (B=-0.058, 95%CI=-0.095, -0.021, p=0.002) and marital status (B=-1.276, 95%CI=-2.525,-0.025, P=0.046). The predictors of attitude were anxiety (B=-0.395, 95%CI=-0.584, -0.206, p<0.001), cigarette smoking (B=4.473, 95%CI=0.992, 7.954, p=0.012) and duration of HIV infection (B=0.371, 95%CI=0.110, 0.631, p=0.005). The predictors of practice were depression (B=-0.176, 95%CI=-0.276, -0.076, p=0.001), cigarette smoking (B=2.200, 95%CI=0.926, 3.474, p=0.001) and duration of HIV infection (B=0.098, 95%CI=0.003, 0.194, p=0.043). Conclusion: Overall, knowledge and practices regarding tuberculosis prevention were good, but attitude was poor. The predictors of knowledge, attitude and preventive practices were age, depression, anxiety, cigarette smoking, monthly income, marital status and duration of HIV infection.